Influence of pH and fuels on the combustion synthesis, structural, morphological, electrical and magnetic properties of CoFe2O4 nanoparticles. (November 2015) - Shanmugavani, A.; Selvan, R.Kalai; Layek, Samar; Vasylechko, Leonid; Sanjeeviraja, C.
Graphical abstract: Abstract: Nanocrystalline spinel cobalt ferrite particles are synthesized by simple combustion method using aspartic acid and glycine as fuels. The single phase cubic structure of CoFe2 O4 is revealed through X-ray diffraction analysis (XRD). Further the Rietveld refinement confirms the formation of inverse spinel structure of CoFe2 O4 . The characteristic functional groups of Co–O and Fe–O are identified from Fourier Transform Infrared (FT-IR) analysis. Uniform distribution of of nearly spherical particles with the size range of 40–80 nm is identified through field emission scanning electron microscope (FESEM) images. The calculated DC conductivity is 1.469 × 10 −7 and 2.214 × 10 −8  S cm −1, for CoFe2 O4 synthesized using aspartic acid and glycine, respectively. The dielectric behavior obeys the Maxwell–Wagner interfacial polarization. The ferromagnetic behavior of CoFe2 O4 is identified using VSM analysis and the calculated coercivity is 27 Oe and saturation magnetization is 68 emu/g.